PENGARUH BELIEFS DAN KEPUASAN PERNIKAHAN TERHADAP KETERLIBATAN AYAH DALAM PENGASUHAN - Zulfa Indira Wahyuni (Pusat Studi Gender dan Anak (PSGA), Universitas Islam Negeri Syarif Hidayatullah, 2020)
Abstract. The father involvement in parenting will have a positive impact on the child's cognitive, emotional and social development. The purpose of this study was to look at the factors that influence the interaction of father and child in parenting, especially children of primary school age. The variables studied were the influence of trust on the role of father, marriage satisfaction, father's education, the number of hours worked by the father, and income. This study used a quantitative approach involving 119 fathers who have elementary school-age children. The sample was taken using a convenience sampling technique. The measuring instruments used are the Inventory of Father Involvement (IFI) from Hawkins et.al (2002), the Role of Father Questionnaire (ROFQ) scale from Palkovitz (1984), and the ERINCH Marital Satisfaction Scale from Fowers and Olson (1993). The data analysis technique used is multiple regression. Based on the results of hypothesis test, the conclusion is that there is a significant influence on the belief role of father, marriage satisfaction, father's education, father's working hours and income. Furthermore, the variables with a significant coefficient value are the belief role of father and marriage satisfaction. Abstrak. Keterlibatan ayah dalam pengasuhan memberikan dampak positif bagi perkembangan kognisi, emosi, dan sosial anak. Tujuan dari penelitian ini adalah untuk melihat faktor-faktor yang mempengaruhi keterlibatan ayah dalam pengasuhan anak, khususnya anak usia Sekolah Dasar. Variabel yang dilihat adalah pengaruh belief role of father, kepuasan pernikahan, pendidikan ayah, jumlah jam kerja ayah, dan pendapatan. Penelitian menggunakan pendekatan kuantitatif dengan melibatkan 119 ayah yang memiliki anak berusia SD. Pengambilan sampel dilakukan dengan teknik convenience sampling. Alat ukur yang digunakan adalah Inventory of Father Involvement (IFI) dari Hawkins dkk (2002), skala The Role of Father Questionnaire (ROFQ) dari Palkovitz (1984), dan skala ERINCH Marital Satisfaction Scale dari Fowers dan Olson (1993). Teknik analisis data yang digunakan adalah regresi berganda. Berdasarkan hasil uji hipoteis, kesimpulan yang pertama adalah ada pengaruh yang signifikan belief role of father, kepuasan pernikahan, pendidikan ayah, jam kerja ayah dan pendapatan. Selanjutnya, variabel yang nilai koefisiennya signifikan adalah belief role of father dan kepuasan pernikahan.